Marketability, profitability, and profit-loss sharing: evidence from sharia banking in Indonesia - Ahmad Abbas; Ainun Arizah (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to analyze marketability constructed from market share and concentration and to test its effect on the profitability and the mediation effects of profit‒loss sharing under stewardship theory.This research employs data of financial statements published by ten sharia commercial banks listed in the Indonesia Financial Services Authority during the period 2011–2016. The data are analyzed into path analysis model using multiple mediators.The result reveals that sharia banks’ marketability in Indonesia tends to be low. Based on the test of significance through Partial Least Square, it is found that marketability has a positive effect on the level of profitability, indicating that market share and concentration of sharia banks positively lead the change on the level of Return on Asset and Return on Equity. This paper further identifies the mediation effects emerged through mudharabah and musharakah. The results point out that mudharabah has a partial effect and musharakah has a competitive effect on the relationship between market share and profitability.This paper can be a decision-maker for Central Bank and Financial Services Authority for encouraging sharia banks to enhance the power market through the mode of finances with profit‒loss sharing.The growth of sharia banks is currently becoming highlight of the literature of sharia banks. This paper provides insights into stewardship theory that sharia banking management provides the concept of the alignment of interest.